Mediação pedagógica e chats educacionais: a tessitura entre colaborar, intermediar e co-mediar - Cerqueira, Valdenice Minatel Melo de (2005)
This work deals with the pedagogical mediation in digital environments for distance learning. More specifically, it tries to understand which characteristics of pedagogical mediation, at web studying chattings, open up conditions to collective contribution. The focus of the research s analysis is an academic subject known as "Teachers formation at digital environments", carried out in 2003, at PUCSP, as part of a major for a stricto sensu Master s degree, and made available to student teachers through TelEduc software. The qualitative research was conducted as a study of case. For the interpretation of chats, the theories of Edgard Morin, José Armando Valente, Mikhail Bakhtin, Paulo Freire and Lev Semenovitch Vygotsky were used as analytical support. The theoretical concepts were articulated so as to establish the analysis foundation as well as to understand the net involving the data and joining the mentioned interpretation. As result of this joint between practice and theory, there have been identified "embroideries" whose texture shows the characteristics of the pedagogical mediation applied in the scope of contribution practices between participants of the referred subject: intermediation, co-mediation, encourage to contribution as well as to reaching autonomy, organization and joint of information, coherence between practice and theory, dialogueness, affection, collaborative work and spiral of learning. The analysis made possible to glimpse the broadness and the limits of educational use of chat, besides the role of mediation in the context of the use of such tool, and the adequacy of this same device to the application of distance learning in postgraduate studies intended for research developments.